2011
DOI: 10.1007/jhep06(2011)117
|View full text |Cite
|
Sign up to set email alerts
|

Higgs and sparticle spectroscopy with Gauge-Yukawa unification

Abstract: We explore the Higgs and sparticle spectroscopy of supersymmetric SU (4) c × SU (2) L × SU (2) R models in which the three MSSM gauge couplings and third family (t-b-τ ) Yukawa couplings are all unified at M GUT . This class of models can be obtained via compactification of a higher dimensional theory. Allowing for opposite sign gaugino masses and varying m t within 1σ of its current central value yields a variety of gauge-Yukawa unification as well as WMAP compatible neutralino dark matter solutions. They inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 67 publications
0
59
0
Order By: Relevance
“…Many groups have explored t−b−τ Yukawa unification (YU) in SUSY theories [6,7,8,9,10,11,12,13]. It has been found that, for µ > 0, YU can occur at the few percent level in either the Higgs splitting (HS) model or the DR3 model (D-term splitting, right-hand neutrino effects and third generation splitting), provided that the GUT scale soft SUSY breaking (SSB) terms are related as …”
Section: Introductionmentioning
confidence: 99%
“…Many groups have explored t−b−τ Yukawa unification (YU) in SUSY theories [6,7,8,9,10,11,12,13]. It has been found that, for µ > 0, YU can occur at the few percent level in either the Higgs splitting (HS) model or the DR3 model (D-term splitting, right-hand neutrino effects and third generation splitting), provided that the GUT scale soft SUSY breaking (SSB) terms are related as …”
Section: Introductionmentioning
confidence: 99%
“…The second class of SO (10) ), whereas the gaugino SSB masses are non-universal at M GUT [32][33][34][35]. In this scenario the desired supersymmetric threshold corrections to t-b-τ Yukawa couplings can be realized with Mg mb [12][13][14][15][16][17].…”
Section: Jhep05(2014)079mentioning
confidence: 99%
“…Finally, we employ the current central value for the top quark mass, m t = 173.3 GeV. Our results are not too sensitive to one or two sigma variation of m t [29].…”
Section: Scanning Procedures and Experimental Constraintsmentioning
confidence: 97%